Protein potential of cushuro (Nostoc sphaericum) gelatinous cyanobacteria powder: an analysis of its protein quality - Delgado-Oblitas, Fernando (2024)
Cushuro (Nostoc sphaericum) is a cyanobacteria whose most notable characteristic is the ability to fix nitrogen from the environment and convert it into proteins, through biochemical processes. Its consumption is promoted mainly in the Andean regions, where its growth is favored by environmental conditions. The objective of this study was to determine the protein quality, moisture content and amino acid profile of cushuro, comparing the latter with the scoring pattern established by the WHO/FAO/UN in 2017 for children, adolescents and adults. Powdered cushuro samples were obtained from 51 kg of fresh cushuro, through drying and grinding processes. Proximate analysis of the components and determination of the amino acid profile were performed using HLPC UV-VIS. The results showed that cushuro contains 30.48 % protein and 1.62 % moisture. On the other hand, the amino acid profile revealed that cushuro partially covered the amino acid intake recommendations established by the WHO/FAO/UN in 2017, with the exception of cysteine, methionine and valine. The cyanobacterium cushuro (Nostoc sphaericum) powder cannot be considered as a high protein quality food due to the presence of limiting amino acids. However, its practicality and versatility in fresh and/or dry form represents many opportunities for its use in hospital gastronomy, vegan enteral formulas, protein modules, among others, as needed.